Handwriting Analysis Using Convolutional Neural Networks - Sadana, Tushar; Jain, Monika; Saxena, Rahul; Kumar, Aashis; Jain, Vidhyanshu; Gupta, Saurabh (International Journal of Engineering and Technology, 2018)
Convolution is the technique to blend or overlap two or more functions. This technique when provided to artificial neural networks, works together to learn the features of different categories of objects and detects them based on its features instead of the shape and edges. This helps to detect the objects even in unusual positions. Since, features of an object remains constant, CNN provides high efficiency significantly better than traditional cascade methods. CNN networks follow convolution, max pooling, flattening. These process combines preprocess the image for training and then the image is transferred to artificial neural networks.Â Â